Building fire safety management analysis based on the reliability assessment method of making safety systems in greenhouse display buildings - Nurjaman, Aceng Galih; Azhar, Moh. (Universitas Wiralodra, 2023)
Fires must be alerted and anticipated or detected as early as possible. If a fire occurs, it will be fatal such as damage to buildings, infrastructure, other facilities and can even result in casualties. Therefore, a reliable fire protection system must be applied. To prevent or anticipate fires, detection must be carried out as early as possible and prepared facilities or infrastructure for fire safety. The Green House display building is an exhibition building of living plants from various mountains in Indonesia including the mountains of Java, the mountains of Sumatra, the mountains of Kalimantan, and the mountains of Papua. This building is the only building in Indonesia, which presents the atmosphere of the mountains exactly the same as the original mountains, both plants, soil and air temperature, but is in a closed room. Plants and soil are taken directly from the associated location. This building is allegedly very prone to fire because there are so many flammable materials such as leaves, wood and others. As well as forests in Indonesia, especially in Kalimantan and Sumatra where fires often occur. Therefore, the application of Building Fire Safety Management in this building must be applied as well as possible. Fire safety management in question includes: completeness of facilities and infrastructure, active protection systems and passive protection systems. Active protection systems such as fire detection devices for this building cannot use ordinary systems, because in this building, the atmosphere is like mountains with many big trees. To ensure that the building can be declared reliable in terms of building safety, especially fire safety, it is necessary to check the reliability of the building. The inspection can be carried out by several methods, including analyzing based on applicable standards and analyzing based on the assessment of the reliability of the building safety system referring to the Settlement Research and Development Center, Research and Development Agency PU, Department of Public Works in 2005 (Pd-T-11-2005-C).